2010
DOI: 10.1095/biolreprod.110.085407
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Expression of KISS1 and Gonadotropin Inhibitory Hormone Genes During the Menstrual Cycle of a Non-Human Primate1

Abstract: Kisspeptin, the product of the KISS1 gene, stimulates gonadotropin-releasing hormone (GnRH) secretion; gonadotropin inhibitory hormone (GnIH), encoded by the RF-amide-related peptide (RFRP) or NPVF gene, inhibits the reproductive axis. In sheep, kisspeptin neurons are found in the lateral preoptic area (POA) and the arcuate nucleus (ARC) and may be important for initiating the preovulatory GnRH/luteinizing hormone (LH) surge. GnIH cells are located in the ovine dorsomedial hypothalamic nucleus (DMN) and parave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
116
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 72 publications
10
116
0
Order By: Relevance
“…The greatest extent of RFRP-3/GnRH fiber colocalization was observed in the ME, where dense GnRH fiber networks were present in the external layer. Although heavy RFRP-ir was seen in the internal layer, projections to the external zone were scarce, suggesting limited hypophysiotrophism as in other mammalian species (14,16,27,(48)(49)(50)(51). Rather than acting on both the pituitary and GnRH neurons as its avian ortholog does (11,13,52,53), it is likely that RFRP-3 acts directly only on GnRH neurons to inhibit NMR reproductive function.…”
Section: Discussionmentioning
confidence: 94%
“…The greatest extent of RFRP-3/GnRH fiber colocalization was observed in the ME, where dense GnRH fiber networks were present in the external layer. Although heavy RFRP-ir was seen in the internal layer, projections to the external zone were scarce, suggesting limited hypophysiotrophism as in other mammalian species (14,16,27,(48)(49)(50)(51). Rather than acting on both the pituitary and GnRH neurons as its avian ortholog does (11,13,52,53), it is likely that RFRP-3 acts directly only on GnRH neurons to inhibit NMR reproductive function.…”
Section: Discussionmentioning
confidence: 94%
“…Rometo et al (610) showed that the estrogenic feedback effect also occurs in women by demonstrating 1) that the increases in GnRH secretion that occurs in postmenopausal women and in ovariectomized cynomolgus macaques (Macaca fascicularis) were associated with increased kisspeptin expression in the arcuate nucleus, and 2) that in ovariectomized monkeys estradiol treatment reversed both effects. In another interesting study (682), kisspeptin mRNA expression in the preoptic area and caudal arcuate nucleus and GnIH mRNA expression in the dorsal medial and paraventricular nuclei were higher in the follicular than the luteal phases of rhesus macaques (Macaca mulatta).…”
Section: Physiological Sex Differences In Disordered Eating)mentioning
confidence: 92%
“…In one study, GnIH was found in the arcuate nucleus in women and female cynomolgus macaques (610); in another study, it was found in the intermediate periventricular (which is adjacent to the dorsomedial nucleus) and paraventricular nuclei in female rhesus macaques (746); and in a third study, it was found in the arcuate, dorsomedial and intermediate periventricular nuclei of female rhesus macaques (682). Interestingly, in the latter study, kisspeptin mRNA expression in the preoptic area and arcuate nucleus and GnIH mRNA expression in the dorsomedial and paraventricular nuclei were higher in the follicular phase than in the luteal phase (682). GnIH fibers project to similar areas as the GnRH neurons, as well as several other brain areas (127,407,745).…”
Section: Physiological Sex Differences In Disordered Eating)mentioning
confidence: 96%
See 1 more Smart Citation
“…Primates may have a surge-generating mechanism different from that in rodents. The mediobasal hypothalamus might play a crucial role in surge induction (13,14).…”
mentioning
confidence: 99%